Design of Information System Monitoring and Evaluation of Primary Health Care Based On Mother Spm - Pratama, Ardhiyan; Sulistiowati, Sulitiowati; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Dinas Kesehatan in Surabaya is a Surabaya city government agencies responsible for public health Surabaya.To achieve the goal of basic health, Dinas Kesehatan Surabaya using the Minimum Service Standards that have been made by the Minister of Health of the Republic of Indonesia. Use of Minimum Service Standards (SPM) in the Primary Health Care is used as a benchmark in achieving the health needs of the Indonesian people, especially maternal health. The solution to the above problems is to make the Design of Information Systems Monitoring and Evaluation of Primary Health Care Based On Mother's SPM is designed to help the coordinator Maternal and Child Health (Kia) and Head of the Section of Health in terms of monitoring and evaluation. So as to achieve minimum service standards in each health center.Keywords: Minimum Service Standards (SPM), Monitoring and Evaluation.